EdPsych Modules - Bohlin, Lisa (New York McGraw-Hill Higher Education, 2012)
"Ed Psych Modules. For ALL your students. Ed Psych Modules speaks to all students regardless of their intended age stage specialization. With four case studies - early childhood, elementary, middle school, and secondary -- for each cluster of modules, your students effectively connect theory and practice using these realistic cases. Written to be used in any order, these modules and clusters give you maximum flexibility in organizing your course. The authors have also limited the use of boxes and other sidebars in order to ensure students identify and understand the core concepts of educational psychology"--
Keywords: Educational psychology. Child development. Learning. Classroom management. Teaching. Education -- Evaluation. EDUCATION -- Educational Psychology